Rancang Bangun Sistem Rekomendasi Teman Belajar Berbasis Web untuk Kolaborasi Akademik Mahasiswa - Bicanro Gebriyan Panjaitan; Lastri Putri Silaban; Azis Kurniadi; Debi Yandra Niska (Infotek: Jurnal Informatika dan Teknologi, 2026)
The advancement of web-based information technology has encouraged the transformation of collaborative learning processes in higher education environments. However, students still experience difficulties in finding suitable study partners due to the absence of a system capable of integrating learning preferences, available schedules, and academic needs in a structured manner. This study aims to design and develop a web-based study partner recommendation system to support students’ academic collaboration through the EduMate platform. The research method used in this study is Research and Development (R&D) with a software development approach using the Prototype method. The research stages include user requirements identification, system requirements analysis, system design, prototype development, system implementation, and system testing using the Black Box Testing method. The system was developed using Node.js and Express.js on the backend side, HTML, CSS, and JavaScript on the frontend side, and MySQL as the primary database. The system also implements Google OAuth authentication, a scoring matching algorithm, study schedule management, automatic notifications, as well as rating and review features. The results of the study indicate that the EduMate system was successfully implemented and is capable of supporting the process of finding study partners in a more effective and structured manner. Based on the Black Box Testing results, all main system features operated according to the specified requirements with a testing success rate of 100%. The system is also able to provide study partner recommendations based on profile compatibility, learning preferences, and user schedules, thereby improving the effectiveness of collaborative learning among students. Therefore, EduMate has the potential to serve as a digital solution in supporting the collaborative learning ecosystem in higher education institutions.